Tailored interventions in a major life decision: A home relocation discrete choice experiment - Joëlle Velvart; Prudence Dato; Florian Kuhlmey (University of Basel, Center of Business and Economics (WWZ), 2022)
Major life decisions such as the choice of housing and its characteristics have significant implications for a household and its energy consumption because they alter structural aspects of energy demand. Energy policy interventions targeting these decisions can therefore have a long-lasting impact. To assess non-monetary policy instruments as incentives for energy-conserving housing choices we implement a discrete choice experiment with a representative sample of Swiss households. The purpose of this paper is the investigation of behavioural differences across households in reaction to social norms and energy-related information. To this end, we distinguish different types of households with a segmentation approach useful for policy makers. Our study provides insights for the question whether the tailoring of non-monetary measures can contribute to a more effective policy design compared to a one-size-fits-all approach. Estimating panel mixed logit models, we find treatment effects to significantly differ across household segments as well as with the baseline energy consumption. The evident treatment heterogeneity suggests a targeted approach for non-monetary interventions.
Keywords: 330; Housing choice; household heterogeneity; non-monetary incentives; social norms; energy literacy